Investigation of chemical profile, biological properties of Lotus corniculatus L. extracts and their apoptotic-autophagic effects on breast cancer cells - Yerlikaya, Şerife; Baloğlu, Mehmet Cengiz; Diuzheva, Alina; Jeko, Jozsef; Cziaky, Zoltan; Zengin, Gökhan (Elsevier BV, 2019)
This study aimed to reveal chemical profiles and biological activities of ethyl acetate (EA), methanol (MeOH), and water extracts of Lotus corniculatus. Ethnobotanical reports have indicated the importance of phytochemical properties of the genus Lotus. In this study, the effects of medicinal plant extracts on antioxidant (DPPH, ABTS, CUPRAC, FRAP, phosphomolybdenum, and metal chelating assays), enzyme inhibitory (on cholinesterase, tyrosinase, a-amylase and a-glucosidase), DNA protection and anticancer properties (including anti-proliferative, cell death and telomerase activity marker gene analysis, apoptotic DNA fragmentation analysis, cell migration test) were evaluated. According to chemical analysis, quercetin derivatives geraldol, isorhamnetin and kaempferol-O-coumaroylhexoside-O-deoxyhexoside isomers were dominant in the extracts. MeOH extracts showed the highest total flavonoids capacity with 21.13 mg RE/g. EA extract showed the strongest anti-amylase activity among the tested extracts. Water extract had the most protective activity against plasmid DNA. To indicate cell survival, MTT test was performed against human MCF-7 and MDA-MB-231 breast cancer cells. Half-maximal inhibitory concentration for cells were calculated and used for detection of mechanisms behind the cancer cell death. EA extract showed up-regulation of Bax proapoptotic gene and apoptotic DNA fragmentation activity on highly invasive MDA-MB-231 cells. Beclin-1 and LC3-II autophagy genes were higly expressed after treatment of MCF-7 cells with EA extracts. EA and MeOH extracts inhibited cell migration ability of both cancer cells. Linoleamide, was dominant component in EA extract and caused apoptosis on MDA-MB-231 breast cancer cells via increasing intranuclear Ca²+. The detailed mechanism behind the anticancer properties should be further investigated.
Keywords: Chemical ingredients; Melanoma, Experimental; Apoptosis; Breast Neoplasms; DNA Fragmentation; Acetates; Antioxidants; Extracts; Mice; Cell Line, Tumor; Autophagy; Animals; Humans; Flavonoids; Methanol; Antineoplastic Agents, Phytogenic; Oxidative Stress; Amylases; Lotus; MCF-7 Cells; Female; Drug Screening Assays, Antitumor; 3. Good health